Bot Canker of Oak in Florida Caused by Diplodia corticola and D. quercivora - Sonja Mullerin; Jason A. Smith (EDIS)
This 6-page fact sheet describes the emergence of these two pathogens of oak and grapevine in North America and Florida; the signs and symptoms of infection; mechanism of host disease and death; fungal morphology; origin, host range, and classification; and management options. Written by Sonja Mullerin and Jason A. Smith, and published by the UF Department of School of Forest Resources and Conservation, March 2015. (Photo: Jason Smith, UF/IFAS)